Evaluating high school electricity consumption and expenditure intensity in the Poudre School District of northern Colorado - Elliott, Jonathan W., author; Guggemos, Angela, advisor; Ore, Janet, committee member; Glick, Scott, committee member (Colorado State University. Libraries, 2010)
With the exception of personnel-related expenditures, utilities represent the largest cost in school budgets, but are one area where expenses can be trimmed without compromising educational quality (Consortium for Energy Efficiency, 2005). In the Poudre School District of Northern Colorado, Fort Collins High School (FCHS) and Fossil Ridge High School (FRHS) have similar building attributes (square footage, mechanical systems, and architectural capacities). In contrast to FCHS (built 1995), FRHS (built 2005) has many energy efficiency features and is LEED-Silver and Energy- Star (2009) certified. Yet in recent years, the electricity costs and electric use intensities (EUIs) were comparable. The purpose of this study was, therefore, to evaluate electricity consumption to understand electric use patterns at these schools. Overall analysis indicated significantly more electricity use for lighting at FCHS (44.04% of total) when compared to FRHS (36.90% to total). Also, HVAC represents 33.16% at FCHS compared to 29.17% at FRHS. However, plug loads account for 24.99% of use at FRHS but only 16.35% at FCHS. Comparing energy performance using whole-building EUI (total annual electric consumption divided by total conditioned floor area) ignores secondary building characteristics that influence consumption. In order to improve the whole building EUI and identify areas of high consumption, individual workspace EUIs were separated for analysis. Variations in workspace specific floor areas and workspace EUIs were seen at both schools. Workspace EUI values ranged from 2.60 kWh/ft2/yr in closet/storage spaces to 40.68 kWh/ft2/yr in the kitchen workspaces. Further, workspace EUIs were partitioned into their HVAC, lighting, plug load, food service and residual components for analysis. Component EUI analysis identified major consumptive differences at the two schools: High for lighting in the trades classrooms and gymnasium at FCHS and high for plug loads in the computer labs at FRHS. Since both high schools have the same educational goals, overly consumptive component EUIs (in one school compared to the other) indicate workspaces where reductions in electric consumption may be possible without detrimental effects on education quality. Educational workspace distribution and the amount of electricity-consuming equipment vary between the schools and hence traditional whole-building EUI (total consumption/total conditioned floor space) must be interpreted with caution. Major differences in the component EUIs observed between the two schools indicated that the high-wattage lighting in the trades classroom and gymnasium at FCHS and the computer density at FRHS should be investigated for possible renovations to reduce electric use at these schools.
Covers not scanned.
Keywords: Electric power consumption -- Colorado -- Fort Collins; High school buildings -- Colorado -- Fort Collins; School buildings -- Energy conservation -- Colorado -- Fort Collins